2019
DOI: 10.1002/jgh3.12276
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopy using back brace support belt: A randomized, prospective trial

Abstract: Background and Aim Looping is a major problem in colonoscopy, and it prolongs procedure time. We evaluated the efficacy and safety of an external abdominal compression device (back brace support belt; Maxbelt) with respect to cecal insertion time and other outcomes. Methods We performed a prospective study on outpatients undergoing elective colonoscopy in Toyoshima Endoscopy Clinic. Subjects were randomly assigned to groups and were subjected to either Maxbelt (n = 39) or no device (control, n = 38) during col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…However, the subgroup analysis revealed that ColoWrap ® significantly reduced the caecal intubation time in obese patients (body mass index of 30-40). Toyoshima et al reported that the encircling the abdominal compression device (Maxbelt ® ) did not significantly decrease the caecal intubation time [7]. However, the subgroup analysis revealed that the Maxbelt ® significantly reduced the caecal intubation time in patients of higher age (age ≥ 45).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the subgroup analysis revealed that ColoWrap ® significantly reduced the caecal intubation time in obese patients (body mass index of 30-40). Toyoshima et al reported that the encircling the abdominal compression device (Maxbelt ® ) did not significantly decrease the caecal intubation time [7]. However, the subgroup analysis revealed that the Maxbelt ® significantly reduced the caecal intubation time in patients of higher age (age ≥ 45).…”
Section: Discussionmentioning
confidence: 99%
“…However, Crockett et al reported inconsistent results [5]. Recently, we conducted an RCT to determine the efficacy and safety of an encircling abdominal compression device (back brace support belt: Maxbelt Ⓡ ) [7]. The intubation time in the Maxbelt group was shorter than that in the control group, but the difference was not significant (3.29 vs. 4.49 min, p = 0.069).…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…This systematic review was performed following Cochrane Handbook for Systematic Reviews of Interventions. 12 The study was reported following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. 15 …”
Section: Methodsmentioning
confidence: 99%